EWMA Control Charts with Intelligent Systems - (:unkn) unknown (SOC ROMANA PENTRU ASIGURAREA CALITATII, 2017)
EWMA control charts are based on the intuitive idea of accumulating information over the time by exponentially discounted weighting of the observations and hence these charts are known to be relatively effective in detecting small to moderate sized shifts in the mean. The inspiration of this study is to present an overview of the EWMA control charting technique suitable for detecting intrusions in quality management. EWMA control charts with intelligent systems are reviewed. Future directions are provided considering recent developments for EWMA control charts.
Keywords: EWMA Control Charts; Average Run Length (ARL); Multivariate EWMA (MEWMA) Control Charts; Intelligent Systems; Fuzzy Logic; AVERAGE CONTROL CHART; WAFER SLICING QUALITY; ECONOMIC DESIGN; NEURAL-NETWORK; OPTIMIZATION; ROBUSTNESS; MODEL